Method and apparatus using selected superparamagnetic labels for rapid quantification of immunochromatographic tests - Mika PA Laitinen (Dove Medical Press, 2009)
Mika PA Laitinen1, Jari Salmela2, Leona Gilbert1, Risto Kaivola1, Topi Tikkala2, Christian Oker-Blom1, Jukka Pekola3, Matti Vuento11Department of Biological and Environmental Science; 2Department of Physics, University of Jyväskylä, Jyväskylä, Finland; 3Low Temperature Laboratory, Helsinki University of Technology, Helsinki, FinlandAbstract: A rapid method and instrumentation for quantification of immunochromatographic tests (ICT) are described. The principle and performance of the method was demonstrated by measuring the levels of human chorionic gonadotropin (hCG) present in urine. The test format was a sandwich assay using two distinct monoclonal antibodies directed against hCG. The first anti-hCG antibody was labeled with superparamagnetic particles whereas the second was immobilized as a narrow detection zone on a porous membrane. The human urine sample was mixed with superparamagnetic particles coated with the first anti-hCG antibody, and the mixture was allowed to migrate past the detection zone containing the second anti-hCG antibody. Capillary forces facilitated migration of the immune complexes along the porous membrane. The amount of superparamagnetic particle-labelled monoclonal anti-hCG bound to the detection zone was directly proportional to the amount of hCG present in the sample as detected by measuring magnetization in the detector coil. The method had a practical detection limit of 20 U/l (54 nM) of hCG per 5 μl of human urine and a linear range of three decades from 20 U/l to 10 000 U/l. In addition, the analysis was completed within less than 10 minutes. Thus, the test format should be suitable for fast detection and monitoring of a large variety of clinically important parameters and analytes.Keywords: affinity, biosensor, hCG, immunochromatography, magnetization, superparamagnetic